Post-Liberal Statebuilding in Central Asia : Imaginaries, Discourses and Practices of Social Ordering - Lottholz, Philipp (Book collections on Project MUSE., 2022)
EPDF and EPUB available Open Access under CC-BY-NC-ND licence.Drawing on decolonial perspectives on peace, statehood and development, this illuminating book examines post-liberal statebuilding in Central Asia. It uses ethnographic fieldwork in Southern Kyrgyzstan to offer a detailed examination of community security and peacebuilding discourses and practices. Through its analysis, the book highlights the problem with assumptions about liberal democracy, modern statehood and capitalist development as the standard template for post-conflict countries, which is widespread and rarely reflected upon.